Taking Systems Thinking to the Global Level: Using the WHO Building Blocks to Describe and Appraise the Global Health System in Relation to COVID‐19. Issue 2 (19th March 2022) - Borghi, Josephine; Brown, Garrett W.
Abstract: Adequately preparing for and containing global shocks, such as COVID‐19, is a key challenge facing health systems globally. COVID‐19 highlights that health systems are multilevel systems, a continuum from local to global. Goals and monitoring indicators have been key to strengthening national health systems but are missing at the supranational level. A framework to strengthen the global system—the global health actors and the governance, finance, and delivery arrangements within which they operate—is urgently needed. In this article, we illustrate how the World Health Organization Building Blocks framework, which has been used to monitor the performance of national health systems, can be applied to describe and appraise the global health system and its response to COVID‐19, and identify potential reforms. Key weaknesses in the global response included: fragmented and voluntary financing; non‐transparent pricing of medicines and supplies, poor quality standards, and inequities in procurement and distribution; and weak leadership and governance. We also identify positive achievements and identify potential reforms of the global health system for greater resilience to future shocks. We discuss the limitations of the Building Blocks framework and future research directions and reflect on political economy challenges to reform.